Inclusion of people with disabilities in the Peruvian labor market [Inclusión de las personas con discapacidad en el mercado laboral peruano] - Velarde-Talleri, Andrés (2018)
ABSTRACT The inclusion of people with disabilities (PWD) in the workplace is a matter currently under discussion. In this context, this research seeks to characterize the inclusion of PWD in the Peruvian labor market. To the effect, a mixed methods study design was developed, which involved the application of an electronic survey to 188 managers and heads of human resources in Peruvian companies. Afterwards, semi-structured interviews were conducted with 12 key informants. The results indicate that the inclusion of PWD in accordance with the provisions of Peruvian law is not met. However, most of the respondents indicate their compliance, in addition to showing a favorable position for hiring PWD. On the other hand, most of the interviewees affirmed that the low labor participation of PWD results from the absence of national control mechanisms and practical devices that companies can use for the hiring of PWD and their inclusion in the workplace.